The influence of the food environment on overweight and obesity in young children: a systematic review. Issue 6 (18th December 2012) - Osei-Assibey, George; Dick, Smita; Macdiarmid, Jennie; Semple, Sean; Reilly, John J; Ellaway, Anne; Cowie, Hilary; McNeill, Geraldine
Abstract : Background and objective: The increasing prevalence of childhood obesity has led to interest in its prevention, particularly through school-based and family-based interventions in the early years. Most evidence reviews, to date, have focused on individual behaviour change rather than the 'obesogenic environment'. Objective: This paper reviews the evidence on the influence of the food environment on overweight and obesity in children up to 8 years. Data sources: Electronic databases (including MEDLINE, EMBASE, Cochrane Controlled Trials Register (CCTR), DARE, CINAHL and Psycho-Info) and reference lists of original studies and reviews were searched for all papers published up to 31 August 2011. Study selection: Study designs included were either population-based intervention studies or a longitudinal study. Studies were included if the majority of the children studied were under 9 years, if they related to diet and if they focused on prevention rather than treatment in clinical settings. Data extraction: Data included in the tables were characteristics of participants, aim, and key outcome results. Quality assessment of the selected studies was carried out to identify potential bias and an evidence ranking exercise carried out to prioritise areas for future public health interventions. Data synthesis: Thirty-five studies (twenty-five intervention studies and ten longitudinal studies) were selected for the review. There was moderately strong evidence to support interventions on food promotion, large portion sizes and sugar-sweetened soft drinks. Conclusions: Reducing food promotion to young children, increasing the availability of smaller portions and providing alternatives to sugar-sweetened soft drinks should be considered in obesity prevention programmes aimed at younger children. These environment-level interventions would support individual and family-level behaviour change.